Jiang Tang Xiao Ke Granule Protects Hepatic Tissue of Diabetic Mice Through Modulation of Insulin and Ras Signaling - A Bioinformatics Analysis of MicroRNAs and mRNAs Network - Ying Bai; Xueli Bao; Guangjian Jiang; Dongyu Ge; Weipeng He; Dandan Zhao; Yi Zhang; Ruijuan Dong; Jing Hua; Nan Yang; Fangfang Mo; Sihua Gao (Frontiers Media S.A., 2020)
ObjectiveTo investigate the impact of JTXK granule on the miRNA expression profiles in hepatic tissue of diabetic mice, and to explore the molecular targets and associated signaling pathways of JTXK granule in its anti-diabetic effect.MethodsEight mice were randomly selected as normal group fed with chow diet. Then high fat diet was used to induce diabetic model, and the mice were subsequently divided into JTXK-treated group (J group, n = 6) and model group (M group, n = 6). After 8 weeks' intervention we examined the fasting blood glucose and observed the histopathologic changes in hepatic tissue between these two groups. Next we screened the differentially expressed miRNAs between the two groups using microRNA sequencing analysis. Finally, miRNA target gene prediction, GO and KEGG analysis were applied to explore the function of DEMs.ResultsThe blood glucose level in J group was significantly lower than M group (P < 0.05). The results from H&E staining showed that the arrangement and structure of hepatocytes from J group were basically normal with fewer ballooning degeneration and less inflammatory cell infiltration. Furthermore, a total of 33 significantly differentiated miRNAs were detected in comparison between the two groups (| log2(fold change) | >0.3, P < 0.05). MiRNA-mRNA analysis showed that mmu-miR-30a-5p, mmu-miR-23b-5p, mmu-miR-199a-5p, mmu-miR-425-5p, and mmu-miR-214-3p are closely related to inflammatory response, histological changes and insulin signal transduction in liver. In addition, KEGG analysis showed that the DEMs were closely related to Ras and insulin signaling pathway.ConclusionJTXK granule exerts anti-diabetic effect in hepatic tissue of diabetic mice by modulating miRNAs and mRNAs network.